Derivation of Kinetic Equations for Free-Radical Nonbranched-Chain Processes of Hydrocarbon and Hydrogen Oxidation (International Journal of Innovative Research in Computer Science & Technology, 2022)
The derivation of kinetic equations for  the oxidation processes by the free-radical  nonbranched-chain mechanism is shown. This derivation is  based on the proposed reaction scheme for the initiated  addition of free radicals to the multiple bond of the  molecular oxygen includes the addition reaction of the  peroxyl free radical to the oxygen molecule to form the  tetraoxyl free radical. This reaction competes with chain  propagation reactions through a reactive free radical. The  chain evolution stage in this scheme involves a few of free  radicals, one of which (tetraoxyl) is relatively low-reactive  and inhibits the chain process by shortening of the kinetic  chain length. The rate equations (containing one to three  parameters to be determined directly) are deduced using  the quasi-steady-state treatment. The kinetic description  with use the obtained rate equations is applied to the  γ-induced nonbranched-chain processes of the free-radical  oxidation of liquid o-xylene at 373 K and hydrogen  dissolved in water containing different amounts of  dioxygen at 296 K. The ratios of rate constants of  competing reactions and rate constants of addition  reactions to the molecular oxygen are defined. In these  processes the oxygen with the increase of its concentration  begins to act as an oxidation autoinhibitor (or an  antioxidant), and the rate of peroxide formation as a  function of the dissolved oxygen concentration has a  maximum. It is shown that a maximum in these curves  arises from the competition between hydrocarbon (or  hydrogen) molecules and dioxygen for reacting with the  emerging peroxyl 1:1 adduct radical. From the energetic  standpoint possible nonchain pathways of the free-radical  oxidation of hydrogen and the routes of ozone decay via the reaction with the hydroxyl free radical in the upper  atmosphere (including the addition yielding the  hydrotetraoxyl free radical, which can be an intermediate  in the sequence of conversions of biologically hazardous  UV radiation energy) were examined. The energetics of the  key radical-molecule gas-phase reactions is considered.
Keywords: Low-Reactive Radical; Autoinhibitor; Competition; Thermochemical Data; Hydrogen; Energy